Researches on reactor core in Heavy ion inertial fusion - Kondo, S.; Karino, T.; Iinuma, T.; Kato, H.; Kubo, T.; Kawata, S.; Ogoyski, A. I. (21st International Symposium on Heavy Ion Inertial Fusion. Autonomous Organization of Education “Nazarbayev University”, 2016)
In Heavy ion inertial fusion (HIF), the issues include the generation and transport of heavy ion beam (HIB), the optimum pellet structure, the realistic nuclear fusion reactor design, etc. In this research, we have studied a conceptual design of a nuclear fusion reactor system in HIF (see Fig. 1)...
Keywords: reactor core; heavy ion inertial fusion; ion beam; Research Subject Categories::NATURAL SCIENCES::Physics::Elementary particle physics